Application of dispersive liquid-liquid microextraction based on solidification of floating organic droplet in the analysis of anti-depressant drugs - Siti Umairah , Mokhtar (2011)
A new simple and rapid sample preparation method based on dispersive liquid-liquid microextraction-solidification of floating organic drop (DLLME-SFO) combined with gas chromatograph-mass spectrometry (GC-MS) has been developed for the extraction and analysis of anti-depressant drugs in water samples. The DLLME-SFO method uses organic solvent with low density and less toxicity. In the method, the disperser solvent (0.5 mL acetonitrile) containing 30 tL n-hexadecane was rapidly injected by a syringe into the 5.0 mL water in a glass tube. Upon centrifugation for 7 min at 3500 rpm, the glass tube was transferred into a beaker containing crushed ice for cooling step. After 5 mm, the solidified n-hexadecane solvent was transferred into a conical vial, where its melts quickly at room temperature and 2 L of it is injected into a gas chromatograph for analysis. Several DLLME-SFO parameters were optimized, including the type and volume of the extraction solvent and disperser solvent, extraction time and salt effect. Under optimum conditions, the method showed good linearity in the range of 0.04 to 0.12 pg/mL for amitriptyline and chlorpromazine, with correlation of determination (r) in the range of 0.992 to 0.995. The limits of detections (LODs) were in the range 0.0085 to 0.0285 igImL. The extraction recoveries of amitriptyline and chlorpromazine from water samples at spiking level of 0.08 tg!mL were 71.34 to 73.52% and 73.83 to 91.09%, respectively. The relative standard deviations (RSDs) were in the range of 4.97 to 6.85% for amitriptyline and 4.84 to 7.49% for chlorpromazine. The method was successfully applied to the determination of antidepressant drugs in drinking water, lake water and tap water samples.